2012
DOI: 10.1016/j.bmcl.2012.08.108
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HIV-1 activity of resveratrol derivatives and synergistic inhibition of HIV-1 by the combination of resveratrol and decitabine

Abstract: Ribonucleotide reductase inhibitors enhance the anti-HIV-1 activities of a variety of nucleoside analogs, including those that act as chain terminators and those that increase the HIV-1 mutation rate. However the use of these ribonucleotide reductase inhibitors is limited by their associated toxicities. The hydroxylated phytostilbene resveratrol has activity in a host of systems including inhibition of ribonucleotide reductase and has minimal toxicity. Here we synthesized derivatives of resveratrol and examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 25 publications
(26 reference statements)
3
65
0
Order By: Relevance
“…We have previously demonstrated that RV, which had no direct antiviral effects against wild-type HIV-1 or against thymidine or adenosine analog-resistant mutants, enhances the antiviral activity of NRTIs [3, 4]. Clouser et al have shown that RV and nucleoside analog decitabine are synergistic against HIV-1 [13]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that RV, which had no direct antiviral effects against wild-type HIV-1 or against thymidine or adenosine analog-resistant mutants, enhances the antiviral activity of NRTIs [3, 4]. Clouser et al have shown that RV and nucleoside analog decitabine are synergistic against HIV-1 [13]. …”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that enterohepatic recirculation through biliary secretion of metabolites and subsequent deconjugation by gut microflora could explain the in vivo activity of RV [22]. In an effort to boost RV bioavailability, several derivatives and delivery approaches are being pursued [13, 23, 24]. …”
Section: Discussionmentioning
confidence: 99%
“…It is a significant component of red wine and has been suggested to explain the “French paradox” in which the southwestern population of France has a low occurrence of coronary heart diseases and cardiovascular diseases despite a high saturated fat diet (Renaud and de Lorgeril, 1992). It has anti-cancer (Udenigwe et al , 2008), anti-inflammatory (Chen et al , 2005a; Udenigwe et al , 2008), antiapoptotic (Baarine et al , 2011; Nicolini et al , 2001), antioxidant (Chang et al , 2012; Spanier et al , 2009), antidiabetic (Chang et al , 2012), and antiviral (Clouser et al , 2012) properties. It is a potent activator of SIRT1 by lowering SIRT1’s Michaelis constant for its acetylated substrate and NAD + (Howitz et al , 2003).…”
Section: Pharmacologic Therapiesmentioning
confidence: 99%
“…Antiviral effects of RSV have been investigated in several human and animal viruses including influenza A virus (Palamara et al., 2005), Epstein‐Bar virus (Chen, Qiao et al., 2012), herpes simplex virus (Chen, Qiao et al., 2012), HIV (Clouser et al., 2012), and hepatitis C virus (Nakamura et al., 2010). Results from most of these studies indicate that RSV can prevent inhibiting protein synthesis and thus inhibit virus proliferation (Yang et al., 2015).…”
Section: Resveratrol and Diseasesmentioning
confidence: 99%